The Turning Point: Scientific Creativity Assessment and Its Relationship with Other Creative Domains in First Year Secondary Students - I. Pont-NiclÃ²s; A. MartÃn-Ezpeleta; Y. Echegoyen-Sanz (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2023)
Research on creativity, as well as its application to the education field and its assessment at the different educational stages, have been of increasing interest over the past decades in different countries. In this context, this study aims to evaluate performance in scientific creativity and its relationship with other creativity domains (linguistic and general creativity) of Spanish first-year secondary students. This is a key moment both from the point of view of the change in educational level and a critical age in cognitive developments associated with creativity. The research was carried out using a quantitative, descriptive, cross-sectional design. Data was collected using previously validated tests. Results revealed a moderate-to-low performance for the scientific domain, as well as for the linguistic one and for general creativity. In addition, positive correlations have been found between all the studied domains of creativity. Nevertheless, this correlation was stronger between both scientific creativity dimensions (daily and specific). This research shows the scarce creative competence of students at the early stage of secondary education and gives evidence about the multicomponent nature of creativity. The need for the inclusion of creative teaching strategies at the secondary education level via transdisciplinary approaches is discussed.